An investigation into requirement of mobile app for apartment residents - Haini, Mohammad Shazreen; Mon, Chit Su; Shibghatullah, Abdul Samad; Jalil, Abdurrahman; Subaramaniam, Kasthuri; Amir Hussin, Amir 'Aatieff (International Journal on Advanced Science, Engineering and Information Technology, 2019)
High-rise residential buildings, such as apartments, flats, and condominiums, are places of shelter for humans, just like any other types of houses. In a high-rise residential block, the building management plays a vital role in keeping the place pristine and habitable for its residents. Research shows that effective communication and harmonious relationship between the building management and the residents are crucial in maintaining a high-rise residential building. A solution needs to be proposed to alleviate this challenge. Traditionally, the mode of information dissemination and communication between the residents and the building management is done manually using information boards and feedback forms. However, their effectiveness, reliability and reach-ability are questionable. With the increasing adoption of mobile devices and cloud computing in today’s scenario, the application of mobile technologies such as mobile applications has become viable as a solution to many real-world problems. This research studies how information about the happenings around the high-rise residential area is conveyed to the residents that is deemed as an essential part of the communication between the building management and the residents. This study aims to improve overall communication efficiency between the residents and the management parties of high-rise residential buildings by introducing a mobile app for apartment residents. Two data collection methods – observation and questionnaire – were used in this study and inspections were carried out in this research. Representations were made to investigate how the residents of a high-rise building receive information about happenings around the apartment complex and how the building management and residents committee communicate to share the information. The questionnaire survey was distributed to Facebook groups of high-rise residential buildings, particularly those staying in Sri Bahagia Court and Angkasa Condominium, as well as UCSI University network. Based on the results collected from participants, most of the communication was through physical noticeboard or online social media platforms such as Facebook. Hence, this research investigates the requirement of a mobile app and proposes the development of a mobile app for apartment residents (MyAPT), which addresses the problems of information sharing and further improves communication among the residents and management of high-rise buildings.